Developing Independent Attitudes in the Pancasila Student Profile Through the 'Little Doctor' Extracurricular Activity - Mahmudah, Nadza Naimatul; Usman, Asep Tutun; Holis, Ade; Amirudin, Jafar (STAI Publisistik Thawalib Jakarta, 2025)
An independent attitude is an attitude that every individual must possess. Independence is an attitude that does not depend on others and can carry out activities well. The existence of a little doctor extracurricular in the school environment is expected to be a place for students to develop their independent attitude by participating in activities provided by educators. This study uses a descriptive qualitative method to describe instilling an independent character through the little doctor extracurricular activity and by the P5 values of the Merdeka curriculum. Then, based on the results of the study, it shows that the seven strategic activities that were born can improve the development of the independent attitude character of students in their school environment, and can be an example of other extracurricular teaching methods that can be periodically applied. Among them are 1. Introduction and manufacture of herbal medicine from natural ingredients. 2. Observation of Health Education Videos 3. Making educational videos. 4. Education on introducing types of waste using Problem-Based Learning techniques and recycling waste. 5. Making sculpture crafts from recycled paper. 6. Explore the Indonesian Red Cross using the role-playing method. 7. Evaluation of material using the games-based learning method. With the birth of this activity, there is an increase in the attitudes of students based on the results of observations of attitude values before and after the implementation of the activity.